Placental Blood Drainage Shortens Duration of the Third Stage of Labor in Women Slowly Administered 20 IU Oxytocin - Metin Kaba; Yaprak Engin Üstün; Elif Gül Yapar Eyi; Hakan Timur; Bekir Serdar Ünlü; Ayşegül Öksüzoğlu (Medical Network, 2017)
Objective: Prolongation of the third stage of labor may cause serious postpartum complications. Thus, timely expulsion of the placenta is essential for preventing complications of the third stage of labor. We conducted a prospective cohort study to determine the effect of placental cord drainage on the duration of the TSL in women administered intravenous oxytocin during this stage. Study Design: This was a prospective cohort study in which 112 low risk pregnant women were allocated to the study. There were 53 women in the placental cord drainage group, and 59 women in the cord clamping group without drainage. Immediately after fetal delivery, intravenous infusion of 20 IU oxytocin in 500 mL Ringers' Lactate was started and infused within 2 hours in women in both groups. Outcome measures were the third stage duration and hemoglobin differences between admission and the postpartum sixth hour. Results: There were no significant differences between the two groups with regard to duration of stages 1 and 2 of labor, hemoglobin level on admission, and at the postpartum sixth hour, and hemoglobin differences between admission and the postpartum sixth hour. The median third stage duration in the study group was 3.40 (range: 0.35-16.20) minutes, and 5.10 (range: 2.30-11.00) minutes in the control group. This difference between the groups was statistically significant (p<0.01). Conclusion: Placental cord drainage reduces the third stage duration following vaginal deliveries in patients receiving intravenous oxytocin. Placental cord drainage is simple, does not require additional cost, and is applicable for every delivery.